GREEN INFRASTRUKTUR IN THE GLOBAL ERA - Adelia Nur Safitri; Conny Damayanty; Andri Indrawan (PT. Antis International Publisher, 2024)
This research aims to determine the development and implementation of green infrastructure, regulations and policies on green infrastructure as well as challenges, obstacles and solutions to green infrastructure in Indonesia. Sustainable development that pays attention to the environment in the era of globalization is very important to be implemented, this is in line with the Sustainable Development Goals (SDGs) which are a global reference to achieve a better and sustainable life. One of the SDGs targets is goal number 9 regarding